BENTUK MEDIA EDUKASI PERILAKU SEKSUAL BERISIKO UNTUK REMAJA TINGKAT SEKOLAH MENRENGAH PERTAMA DI KABUPATEN BADUNG PROPINSI BALI - Moh. Fairuz Abadi (Bali Medika Jurnal, 2017)
Health promotion is a process to build self  awareness to avoid of the health risk. Education about sexual risk behavior for teenagers is one of them. Education media had a function to communicate and  spread the information of  health. The education  media on sexual risk behavior for teenagers was a important thing for health promotion programe. The research pupouse are to expose and describes the form of education media on sexual risk behavior for teenagers at junior high schools in Badung Regions by using qualitaive method. The respondens are choice by purposive. The result shown that there is many form of education  media for sexual risk behavior for teenagers, wich are booklet, power poin slide, leaflet/brocure, social media, video, TV,book  and  peer.  Media that was ever used are  booklet, power poin slide, leaflet/brocure, social media and article. Media that was more used are  social media, leaflet/brocure and  power poin. There is no information about the effectivity level of  media.  The outcame of  education media for sexual risk behavior only increase cognitive aspect.  Based from  all of respondens speaks, media which is suitable are slide/power poin, leaflet/brocure, sosial media dan video.